A national cohort study and confidential enquiry to investigate ethnic disparities in maternal mortality - Marian Knight; Kathryn Bunch; Nicola Vousden; Anita Banerjee; Philippa Cox; Fiona Cross-Sudworth; Mandish K. Dhanjal; Jenny Douglas; Joanna Girling; Sara Kenyon; Rohit Kotnis; Roshni Patel; et al. (EClinicalMedicine, 2022)
Summary: Background: Ethnic disparities in maternal mortality were first documented in the UK in the early 2000s but are known to be widening. This project aimed to describe the women who died in the UK during or up to a year after the end of pregnancy, to compare the quality of care received by women from different aggregated ethnic groups, and to identify any structural or cultural biases or discrimination affecting their care. Methods: National surveillance data was used to identify all 1894 women who died during or up to a year after the end of pregnancy between 2009 and 18 in the UK. Their characteristics and causes of death were described. A Confidential Enquiry was undertaken to describe the quality of care women received. The care of a stratified random sample of 54 women who died during or up to a year after the end of pregnancy between 2009 and 18, (18 from the aggregated group of Black women, 19 from the Asian aggregated group and 17 from the White aggregated group) was re-examined specifically to describe any structural or cultural biases or discrimination identified. Findings: There were no major differences causes of death between women from different aggregated ethnic groups, with cardiovascular disease the leading cause of death in all groups. Multiple areas of bias were identified in the care women received, including lack of nuanced care (notable amongst women from Black aggregated ethnic groups who died), microaggressions (most prominent in the care of women from Asian aggregated ethnic groups who died) and clinical, social and cultural complexity (evident across all ethnic groups). Interpretation: This confidential enquiry suggests that multiple structural and other biases exist in UK maternity care. Further research on the role of microaggressions is warranted. Funding: This research is funded by the National Institute for Health Research (NIHR) Policy Research Programme, conducted through the Policy Research Unit in Maternal and Neonatal Health and Care, PR-PRU-1217–21,202. MK is an NIHR Senior Investigator. SK is part funded and FCS fully funded by the National Institute for Health Research (NIHR) Applied Research Centre (ARC) West Midlands. The views expressed are those of the author(s) and not necessarily those of the NIHR or the Department of Health and Social Care.